2016
DOI: 10.1016/j.ijfatigue.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A crystal plasticity-based study of the relationship between microstructure and ultra-high-cycle fatigue life in nickel titanium alloys

Abstract: Nickel Titanium (NiTi) alloys are often used in biomedical devices where failure due to mechanical fatigue is common. For other alloy systems, computational models have proven an effective means of determining the relationship between microstructural features and fatigue life. This work will extend the subset of those models which were based on crystal plasticity to examine the relationship between microstructure and fatigue life in NiTi alloys. It will explore the interaction between a spherical inclusion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 53 publications
(93 reference statements)
1
13
0
Order By: Relevance
“…The main difference between both results is the higher overall strain amplitude level, which was found for cyclic loaded PVAs. This fatigue strain effect attributed to the existence of voids is in good agreement with results by Moore et al [32] and Kafka et al [33], which observed a strong drop in fatigue initiation lifetime based on numerical evaluation methods for PVAs. By analyzing the effect of varying mean strain on the strain amplitude in the bottom of Fig.…”
Section: General Overviewsupporting
confidence: 92%
“…The main difference between both results is the higher overall strain amplitude level, which was found for cyclic loaded PVAs. This fatigue strain effect attributed to the existence of voids is in good agreement with results by Moore et al [32] and Kafka et al [33], which observed a strong drop in fatigue initiation lifetime based on numerical evaluation methods for PVAs. By analyzing the effect of varying mean strain on the strain amplitude in the bottom of Fig.…”
Section: General Overviewsupporting
confidence: 92%
“…inclusion was also modeled, providing two extreme cases. It has been reported that particle void assemblies (PVAs) are in fact the worst-case condition (Ref 22,24) and warrant modeling in the future work. FEA studies have also shown that the morphology of the inclusions (size and shape) plays a role in influencing the fatigue life of Nitinol compared to inclusion material type and inclusion-inclusion interactions (Ref 24, 25).…”
Section: Discussionmentioning
confidence: 99%
“…A Fatemi-Socie fatigue indicating parameter, akin to that described in Ref. [27], is then used to determine regions or high fatigue initiation potency.…”
Section: Void Clustermentioning
confidence: 99%